Financial delusions and the persistence of capital - Fabio Vighi (Finance and Society, 2023)
The dominant view among critics of today's financial economy is that, at one point in its long history, capitalism took the wrong turn, falling victim to greed and corruption. This view is fundamentally flawed. The elementary but disavowed reason for the current dominance of the financial sector is that the social narrative based on labour exploitation has grown impotent. The law of value is artificially kept alive in spite of its vanishing. But how long can such delusion last?
Keywords: 300; capital; delusion; Finance; implosion; labour; work